An Observational Study of Trifluridine/Tipiracil-Containing Regimen Versus Regorafenib-Containing Regimen in Patients With Metastatic Colorectal Cancer - Hsieh, Meng-Che; Rau, Kun-Ming; Lin, Shung-Eing; Liu, Kuang-Wen; Chiu, Chong-Chi; Chen, Chih-I; Song, Ling-Chiao; Chen, Hsin-Pao (Frontiers in Oncology, 2022)
Background There are no randomized control trials comparing the efficacy of trifluridine/tipiracil and regorafenib in patients with metastatic colorectal cancer (mCRC). Herein, we conducted an observational study to compare the oncologic outcomes of trifluridine/tipiracil-containing regimen (TAS-102) and regorafenib-containing regimen (REG) in patients with mCRC. Material and method Patients who were diagnosed to have mCRC in 2015 to 2021 and treated with TAS-102-containing regimen or REG-containing regimen were recruited. Monotherapy or combination therapy were all allowed in this study. Oncologic outcomes were presented with progression-free survival (PFS), overall survival (OS), overall response rate (ORR) and disease control rate (DCR). Results A total of 125 patients were enrolled into our study, accounting for 50 patients with TAS-102 and 75 patients with REG. Of these patients, 64% were treated with TAS-102 or REG monotherapy, while the remaining were treated with TAS-102 combination or REG combination. In general, the median PFS and OS were 3.7 versus 2.0 months (P = 0.006) and 9.2 versus 6.8 months (P = 0.048) in TAS-102 and REG, respectively. The ORR and DCR were 44% versus 20% (P < 0.001) and 72% versus 43% (P < 0.001) in TAS-102 and REG, respectively. As for treatment strategies, the survival were significantly longer in combination than in monotherapy, no matter in TAS-102 or REG group. Multivariate analysis showed TAS-102 and combination therapy were independent predictor associated with better survival. Conclusions Our results suggested that TAS-102 had better oncologic outcomes than REG in patients with mCRC, especially in combination. Further prospective trials are warranted to confirm our results.